전산화 단층촬영으로 측정한 정상 한국인의 눈물샘 부피 - 민성규; Seong Gyu Min; 하명숙; Myung Sook Ha (Daihan angwa haghoi jabji, 2015)
Purpose: We used computed tomography (CT) scans to describe normal Korean lacrimal gland volume and lacrimal gland size and then examined their correlations with patient age. Methods: CT scans were obtained in 213 orbits of 111 patients who underwent CT from January to August of 2013. Aquarius iNtuition (TeraRecon, Foster City, CA, USA) software was used to outline the lacrimal gland in consecutive axial slices and to calculate the volume. Results: The mean volume of the lacrimal gland was 0.589 cm3 in right orbits (SD = 0.090), 0.583 cm3 in left orbits (SD = 0.289), 0.596 cm3 in males (SD = 0.083), and 0.575 cm3 in females (SD = 0.094). There was no significant difference in mean lacrimal gland volume according to laterality (p = 0.614) or sex (p = 0.102) (2-sample t-tests). We investigated mean lacrimal gland volume in 3 age groups. Mean lacrimal gland volume was 0.630 cm3 (SD = 0.080) for the 20 to 40 year old group, 0.553 cm3 (SD = 0.734) for the 41 to 60 year old group, and 0.544 cm3 (SD = 0.885) for the older than 60 years old group. There was an inverse relationship between gland volume and age (Pearson r = .0.384, p = 0.00). Conclusions: The mean volume of the lacrimal gland decreased with age and there was no significant difference between right and left orbits or between male and female patients. J Korean Ophthalmol Soc 2015;56(1):1-5